2015
DOI: 10.1371/journal.pone.0143846
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Proof-of-Concept Study of Oral QLT091001 in Retinitis Pigmentosa Due to Inherited Deficiencies of Retinal Pigment Epithelial 65 Protein (RPE65) or Lecithin:Retinol Acyltransferase (LRAT)

Abstract: Restoring vision in inherited retinal degenerations remains an unmet medical need. In mice exhibiting a genetically engineered block of the visual cycle, vision was recently successfully restored by oral administration of 9-cis-retinyl acetate (QLT091001). Safety and visual outcomes of a once-daily oral dose of 40 mg/m2/day QLT091001 for 7 consecutive days was investigated in an international, multi-center, open-label, proof-of-concept study in 18 patients with RPE65- or LRAT-related retinitis pigmentosa. Eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 39 publications
(47 reference statements)
1
43
0
Order By: Relevance
“…[55][56][57] In RPGRIP1 knock-out mice, both improved outer segment morphology and photoreceptor survival, and better preservation of ERG responses have been demonstrated with RPGRIP1 gene replacement using both AAV2 and AAV8 vectors. 71 72 Improved photoreceptor function up to 24 months postsubretinal injection has also been shown in the canine model.…”
Section: Rpgrip1-associated Lcamentioning
confidence: 99%
“…[55][56][57] In RPGRIP1 knock-out mice, both improved outer segment morphology and photoreceptor survival, and better preservation of ERG responses have been demonstrated with RPGRIP1 gene replacement using both AAV2 and AAV8 vectors. 71 72 Improved photoreceptor function up to 24 months postsubretinal injection has also been shown in the canine model.…”
Section: Rpgrip1-associated Lcamentioning
confidence: 99%
“…Currently, no approved pharmacological treatment is available, although phase 1b trials of oral 9-cis-retinyl acetate have shown transient increases in Goldmann visual fields area in some participants. 26,27 Here, we report the design, conduct, and safety and efficacy results of a phase 3 study of sequential, bilateral, subretinal administration of voretigene neparvovec in participants with RPE65- mediated inherited retinal dystrophy. To our knowledge, this is the first randomised, controlled, phase 3 study of a gene therapy for a genetic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained using chemically inert and more tolerable 9- cis -retinyl acetate or 9- cis -retinyl succinate that serve as pro-drug forms of 9- cis -retinal [137]. In the initial clinical trial (phase 1b) oral administration of 40 mg/m 2 of 9- cis -retinyl acetate (QLT091001) for seven consecutive days resulted in expansion of functional retinal area in 71% of enrolled LCA patients, 43% displayed improved visual acuity [138,139]. Importantly, these functional changes were associated with healthier retinal morphology measured as thinness of photoreceptor cell outer segments.…”
Section: Mutations In Lrat Gene and Their Clinical Manifestationsmentioning
confidence: 99%